Assume nothing ebook - Haywood, Gar Anthony (2012)
The new novel from the critically acclaimed and award-winning author - When Joe Reddick and his family are threatened in their LA home by a masked, knife-wielding intruder, it means serious trouble for a gang of desperate criminals. The threat sends Joe Reddick over the edge. He's lived the nightmare of losing a family to a crazed killer once, and he's not going to let it happen again. After sending his wife and son to safety, he goes to war, determined to kill those responsible. Soon Reddick's living nightmare will finally be over. One way or the other . . .|The new novel from the critically acclaimed and award-winning author - When Joe Reddick and his family are threatened in their LA home by a masked, knife-wielding intruder, it means serious trouble for a gang of desperate criminals. The threat sends Joe Reddick over the edge. He's lived the nightmare of losing a family to a crazed killer once, and he's not going to let it happen again. After sending his wife and son to safety, he goes to war, determined to kill those responsible. Soon Reddick's living nightmare will finally be over. One way or the other . . .